Interaction between 1,4,8,11-Tetraazacyclotetradecane with Iodine and Bromine in Chloroform Solution - Semnani, A.; Pouretedal, H.R.; Firooz, A. (Asian Journal of Chemistry, 2010)
A spectrophotometric study concerning the interaction between 1,4,8,11-tetraazacyclotetradecane (CYCLAM) with iodine and bromine has been performed spectrophotometrically in chloroform solution at 25ºC. As a helpful guide, the complexation of tetrabutylammonium iodide and tetrabutylammonium bromide with iodine and bromine have also been studied. The results of iodine are indicative of the formation of CYCLAM–I+I−3 through an equilibrium reaction. However, in the case of bromine, the formation of CYCLAM–Br+Br−3 through a non-equilibrium reaction is confirmed. The possible reason for the observation of a non-equilibrium reaction is discussed. The stability constant of the CYCLAM-I2 complex is evaluated from the computer fitting of absorbance-mole ratio data as log Kf = 5.32 ± 0.04. IR spectrum of CYCLAM has been compared with IR spectra of complexes and the effects of complexation on absorption bands are discussed. The comparison of the conductances of solutions containing complexes with solutions of iodine, bromine or CYCLAM indicate that the complexes are mostly in the form of ion pairs.